Electrospun Nanofibers of Natural and Synthetic Polymers as Artificial Extracellular Matrix for Tissue Engineering - Mina Keshvardoostchokami; Sara Seidelin Majidi; Peipei Huo; Rajan Ramachandran; Menglin Chen; Bo Liu (Nanomaterials, 2020)
Many types of polymer nanofibers have been introduced as artificial extracellular matrices. Their controllable properties, such as wettability, surface charge, transparency, elasticity, porosity and surface to volume proportion, have attracted much attention. Moreover, functionalizing polymers with other bioactive components could enable the engineering of microenvironments to host cells for regenerative medical applications. In the current brief review, we focus on the most recently cited electrospun nanofibrous polymeric scaffolds and divide them into five main categories: natural polymer-natural polymer composite, natural polymer-synthetic polymer composite, synthetic polymer-synthetic polymer composite, crosslinked polymers and reinforced polymers with inorganic materials. Then, we focus on their physiochemical, biological and mechanical features and discussed the capability and efficiency of the nanofibrous scaffolds to function as the extracellular matrix to support cellular function.